2016
DOI: 10.1016/j.npep.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high fat diet and estradiol on hypothalamic prepro-QRFP mRNA expression in female rats

Abstract: Estradiol (E2) is a potent regulator of feeding behavior, body weight and adiposity in females. The hypothalamic neuropeptide, QRFP, is an orexigenic peptide that increases the consumption of high fat diet (HFD) in intact female rats. Therefore, the goal of the current series of studies was to elucidate the effects of E2 on the expression of hypothalamic QRFP and its receptors, QRFP-r1 and QRFP-r2, in female rats fed a HFD. Alterations in prepro-QRFP, QRFP-r1, and QRFP-r2 expression across the estrous cycle, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 77 publications
0
15
1
1
Order By: Relevance
“…We found that QRFP neurons are distributed in the basolateral hypothalamic regions, including the tuber cinereum and lateral hypothalamic area, constituting distinct neuronal population from neurons that produce orexin or MCH. It was reported that the expression of QRFP is detected in the arcuate nucleus and ventrolmedial hypothalamus (VMH) in rats [18,22]. However, we did not detect QRFP mRNA or peptide in these regions in this study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…We found that QRFP neurons are distributed in the basolateral hypothalamic regions, including the tuber cinereum and lateral hypothalamic area, constituting distinct neuronal population from neurons that produce orexin or MCH. It was reported that the expression of QRFP is detected in the arcuate nucleus and ventrolmedial hypothalamus (VMH) in rats [18,22]. However, we did not detect QRFP mRNA or peptide in these regions in this study.…”
Section: Discussioncontrasting
confidence: 82%
“…QRFP mRNA was upregulated by fasting, and downregulated when mice were fed a high-fat diet (HFD) [15,21]. HFD feeding increased expression of QRFP mRNA in the hypothalamus of female rats, and estradiol, which is a potent regulator of feeding behavior was shown to increase QRFP [22]. From these observations, we hypothesized that this neuropeptide is involved in the physiological mechanisms of feeding behavior and energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this observation, it has been recently shown that direct administration of 26RFa into the medial hypothalamus increases food consumption (Zagorácz et al, 2015), and that the concentrations of 26RFa/43RFa in the VMH are significantly increased in rats fed a standard chow (Beck and Richy, 2009). It has also been found that 26RFa still stimulates appetite when rats are fed a high fat diet (Primeaux et al, 2008), and this phenomenon is accompanied by an up-regulation of prepro26RFa and GPR103 in the VMH and the Arc (Schreiber et al, 2016). By contrast, these authors (Primeaux et al, 2008; Schreiber et al, 2016) as well as Patel et al (2008) failed to find any effect of 26RFa or 43RFa on food consumption when rats are fed a standard chow.…”
Section: Rfa and Control Of Feeding Behaviormentioning
confidence: 99%
“…It has also been found that 26RFa still stimulates appetite when rats are fed a high fat diet (Primeaux et al, 2008), and this phenomenon is accompanied by an up-regulation of prepro26RFa and GPR103 in the VMH and the Arc (Schreiber et al, 2016). By contrast, these authors (Primeaux et al, 2008; Schreiber et al, 2016) as well as Patel et al (2008) failed to find any effect of 26RFa or 43RFa on food consumption when rats are fed a standard chow. Interestingly, in both mice and rats, 26RFa potently stimulates food intake when the animals are deprived of food for 18 h prior to the injection of the neuropeptide (Chartrel et al, 2003; Do Rego et al, 2006; Lectez et al, 2009) strongly suggesting that starvation potentiates the orexigenic activity of 26RFa.…”
Section: Rfa and Control Of Feeding Behaviormentioning
confidence: 99%
“…QRFP has orexigenic effects in rodents [1][2][3][4][5]. QRFP also regulates behavioral arousal, blood pressure, locomotor activity, and aldosterone and insulin secretion [2,6,7].…”
mentioning
confidence: 99%